Standardisation of soaking and germination time for preparation of germinated brown rice - P, Abhilasha; Pal, US; Nayak, RN; Sahoo, G; Mahapatra, M; Rayaguru, K (ORYZA-An International Journal of Rice, 2022)
A study was undertaken to standardise the soaking and germination time for preparation of germinated brown rice (GBR). Freshly harvested paddy of Prativa variety wasÂ dehusked (dehusked or dehulled) in rubber roll sheller to get brown rice which was soaked in demineralised water followed by germination at 27Â±1oC temperature and 85-90 % relative humidity for different time period. The soaking and germination time were standardised based on moisture content, germination percentage, Gamma-Aminobutyric acid (GABA) content and total microbial load for preparation of germinated brown rice. Germination percentage and GABA content increased significantly with germination time (p<0.05). Soaking of brown rice for 12 h followed by 24 h germination was standardised for preparation of germinated brown rice to get maximum GABA content of 70.3 mg/100 g d.m.